Preserving cultural identity through Islamization of education : implications for Muslim higher education institutions - Ali, Saudullah (Kulliyah of Education, International Islamic University Malaysia, 2016)
The departure of Muslims, in their lifestyles and social behaviours, from the right path of Islam and the resultant loss of adab in Muslim individuals; and the scientific backwardness in Muslim communities indicate that the Ummah is experiencing a crisis in cultural identity. To address this issue, this study argues for the importance of preserving Islamic culture as the cultural identity of the Muslim Ummah and analyses the role of Islamization of education in enhancing the mission of Muslim higher education institutions in the preservation of this cultural identity. The analytical research approach was employed to achieve the purposes of the study. The concepts and ideas related to cultural identity and Islamization of education were grasped by exploring the Muslim intellectual heritage. The problem of Islamic cultural identity among Muslims was examined based on the literature from primary and secondary sources. In order to analyse the role of the agenda of Islamization of education, the study identified first the requirements of the preservation of an Islamic cultural identity. To achieve these requirements and to solve the problem of cultural identity crisis of the Ummah, the study asserts the agenda of Islamization of education which is based on the Islamic philosophy of education and includes Islamization of several aspects of education. In analysing the role of Islamization of education, the practices of International Islamic University Malaysia (IIUM), as a model of Islamization, were analysed. The study found that indications of a crisis in cultural identity exist and internal and external causes or challenges are still working as a threat to cultural identity. It also found that the most important requirements of cultural preservation are achieving the goals and objectives of Islamic culture; fulfilling its functions and providing its components; and maintaining its characteristics. The study further demonstrates that Islamization of education and the practices of Islamization at IIUM have helped to achieve the requirements of preserving Islamic cultural identity. The most important implications derived from the study regarding preserving the Islamic cultural identity are accepting preservation of Islamic cultural identity as an important mission of Muslim higher education institutions; acknowledging the role of Islamization of education in preserving Islamic cultural identity; and implementing the principles and practices of Islamization of education. The most important of these are providing education based on the tawÍīdÊ paradigm and making Islamization and integration as the cores of the vision and the mission; implementing a comprehensive Islamized educational curriculum; generating research and publications with Islamic perspectives; providing non-formal education and awareness programmes from Islamic perspectives; providing co-curricular and extra-curricular activities incorporating Islamic values and ethics; and practising Islamization in educational management and services.